IMPACT OF FADAMA III ADDITIONAL FINANCE II ON YIELD AND INCOME OF FARO-44 RICE FARMERS BENEFICIARIES IN TARABA STATE, NIGERIA - Banseka, R. F.; Murtala, N.; Sani, R. M. (Nigerian Journal of Agriculture and Agricultural Technology, 2024)
The study was carried out to examine the impact of fadama III additional finance II on yield and income of faro-44 rice farmers beneficiaries in Taraba State, Nigeria. A Multi-stage sampling procedure was used to select 500 respondents. Data were analyzed using descriptive statistics (mean, frequency distribution and percentages) and inferential statistics (Gini coefficient). The findings of the study revealed that more days was expended in faro-44 rice weeding days per hectare with mean of 5.0 and 8.0 hours worked/day. The average number of tractors owned by the fadama users’ association (FUA) farmers was 2 with value of N3,129,079.63. The major inputs intervention received by the respondents were 5 kg seeds, wet season = 10 kg seeds all at N10,000/20 kg bag ((dry season), 2 bags of NPK fertilizer and 4 bags of NPK fertilizer at N7,000/50 kg bag in dry and wet season respectively, followed by a bag of Urea fertilizer in dry season and 2 bag of Urea fertilizer at N9,000/50 kg bag in wet season. Similarly, the respondents also received 4 liters of herbicides each in dry season and wet season. The result further revealed that the yield (kg/ha) in dry season increased from 3,675 kg before intervention to 6,156 kg after intervention representing 59.69% increase and with mean difference of 2,481 kg significant at P<0.01. Similarly, yields in wet season by the faro-44 rice farmers has a mean difference of 1,679 kg compared to mean difference of 2,481 yield in dry season. Consequently, income from dry season harvest (N/ha) increased by 40.77% representing Naira value from N787,375.00 to N1,720,400.00 for before and after fadama AF-II intervention. Similarly, income from wet season harvest only increased by 4.63% with wet season mean income difference of N315,189 compared to the dry season mean income difference of N933,025 implying that the respondents realized more income in dry season faro-44 rice farming than wet season in Taraba State, Nigeria. The study concluded that fadama III additional finance II project intervention had positive impact on yield and income of the respondents and faro-44 rice farming yielded more in dry season than wet season. It is recommended that farm inputs at subsidized rate should be made timely available, there should be further collaboration through the State fadama office with National Agricultural Land Development Authority (NALDA) to clear more land, rice promotion programmes like training on modern rice production techniques, new varieties of seeds in order to be technically efficient should also be promoted and farmers should be encouraged to form cooperatives to benefit more from such laudable fadama AF-II intervention and enjoy economies of scale.